A New Chaotic Jerk System with Three Nonlinearities and Synchronization via Adaptive Backstepping Control - Vaidyanathan, Sundarapandian; Kingni, Sifeu Takougang; Sambas, Aceng; Mohamed, Mohamad Afendee; Mamat, Mustafa (International Journal of Engineering and Technology, 2018)
Jerk systems are popular in mechanical engineering and chaotic jerk systems are used in many applications as they have simple structure and complex dynamic properties. In this work, we report a new chaotic jerk system with three nonlinear terms. Dynamical properties of the chaotic jerk system are analyzed through equilibrium analysis, dissipativity, phase portraits and Lyapunov chaos exponents. We show that the new chaotic jerk system has a unique saddle-focus equilibrium at the origin. Thus, the new chaotic jerk system has a self-excited strange attractor. Next, global chaos synchronization of a pair of new chaotic jerk systems is successfully achieved via adaptive backstepping control.